Analisis Prosedur Pembelian dan Negosiasi Bisnis pada PT. Daya Satya Abrasives - Daka Radhiyan Yahya; Sumainah Fauziah (Institut Nalanda, 2023)
Purchasing is the process of finding sources to provide the goods and services a company needs to support its business activities. The purchasing department acts as an intermediary between the purchasing company and the suppliers. Standard Operating Procedure (SOP) is a written document that contains detailed instructions or guidelines on how a task or process must be carried out consistently and efficiently. business negotiation is reaching an agreement that meets the interests and needs of all parties involved. This study uses a qualitative research method, where appropriate data collection is carried out regarding the purchasing procedures and business negotiations that apply at PT. Daya Satya Abrasives. The quality objectives required by the purchasing department include timeliness of arrival, variance, inventory stock. The conclusion that can be drawn is that in the purchasing process there are obstacles faced by the purchasing or purchasing department, such as late delivery schedules from business partners because that is very influential for the company. And there is also a problem with terms of payment where partners refuse to pay credit (7days, 14days, 30days). In dealing with this problem, the purchasing party always follows up or monitors the requested goods so that there are no delays and as much as possible convinces the supplier to get better terms of payment. Keywords: negotiation business, Purchasing, purchasing procedure